Global disparities in drug-related adverse events of patients with multiple myeloma: a pharmacovigilance study - Majid Jaberi-Douraki; Xuan Xu; Danai Dima; Sikander Ailawadhi; Faiz Anwer; Sandra Mazzoni; Jason Valent; Muhammad Hamza Habib; Jim E. Riviere; Shahzad Raza (Blood Cancer Journal)
Abstract Multiple myeloma (MM) is a complex hematological malignancy of clonal plasma cells driven by alterations to the chromosomal material leading to uncontrolled proliferation in the bone marrow. Ethnic and racial disparities persist in the prevalence, diagnosis, management, and outcomes of MM. These disparities are multifaceted and intersect with various factors, including demographics, geography, socioeconomic status, genetics, and access to healthcare. This study utilized the openFDA human drug adverse events (AEs) to analyze global data pertaining to MM patients and patterns of treatment-related AEs. We identified ten most frequently used drugs and drug regimens in six distinct regions, including North America (NA), Europe (EU), Asia (AS), Africa (AF), Oceania (OC), and Latin America & the Caribbean (LA). AE patterns were evaluated using the reporting odds ratio combined with a 95% confidence interval. AE reports were more prevalent in men than in women across all regions. Cardiotoxicities were more likely observed in AS and EU, while secondary neoplasms were more frequently reported in the EU. Nephropathies were prominent in OC, AF (in males), and AS (in females), while vascular toxicity, including embolism and thrombosis, was more common in NA (in males). A notable improvement in survival, particularly in AS, EU, and NA, with a significant decline in death rates was observed. Hospitalization rates displayed less variation in AS and EU but exhibited more pronounced fluctuations in AF, LA, and OC. In conclusion, this comprehensive analysis offers valuable insights into the demographic, geographic, and AE patterns of MM patients across the globe.